Lethal and sublethal effects of botfly (Philornis seguyi) parasitism on House Wren nestlings - Quiroga, Martin Anibal (2012)
We studied the effect of botfly (Philornis seguyi) parasitism on survival and growth of House Wren (Troglodytes aedon) nestlings. We investigated whether nestling survival was related to (1) the intensity of botfly infestation, (2) age of the nestling at the time it was parasitized, and (3) the order in which a chick hatched within a brood. The prevalence of botfly parasitism was 25%; the mean intensity and age at parasitism were 12.8 larvae per nestling and 3.9 days, respectively. Nestling survival was 42% lower in infested than in noninfested broods. Nestling survival was negatively associated with the mean intensity of parasitism of the brood and positively associated with the age of the nestling at the time it was parasitized. Within infested broods, nestling survival was higher in chicks hatched first than in chicks hatched last. Infested nestlings that survived until fledging grew at lower rates and remained in the nest longer than did nestlings in noninfested broods. Our results reveal that P. seguyi has lethal and sublethal effects on House Wren nestlings and that the intensity of parasitism, age of nestlings at the time they are infested, and sequence of hatching are important factors that influence the survival of parasitized nestlings. © The Cooper Ornithological Society 2012.